Benefit of wakeful resting on gist and peripheral memory retrieval in healthy younger and older adults. (13th July 2019) - Sacripante, Riccardo; McIntosh, Robert D.; Della Sala, Sergio
Highlights: Younger adults outperformed older adults on peripheral but not on gist memory. Wakeful resting increased performance both on peripheral and gist memory. Wakeful resting equally benefitted gist and peripheral memory in younger adults. Wakeful resting benefitted gist more than peripheral details in older adults. Abstract: Retrieval is greater if new learning is followed by a period of wakeful rest, minimising the likelihood of retroactive interference. It is not known if this benefit extends to recollection of both gist and peripheral details, nor whether age affects the benefit of wakeful resting in either of these types of recollection. Forty-five younger and forty older adults were presented with prose passages for later recall followed by a period of either interference or wakeful resting. Younger participants outperformed older participants in remembering peripheral details, but not on gist memory. Wakeful resting led to higher overall recollection in both age groups, both for gist and for peripheral details. Also, wakeful resting was more beneficial for gist than peripheral memory in older but not younger adults. We discuss these novel findings and their theoretical implications for a memory consolidation account of the benefits of wakeful resting.